Effect of Cost Leadership Strategies on the Financial Performance of SACCOs in Kirinyaga County, Kenya - Njoroge, Winnifred Wairimu; Kamau, Stephen; Maina, Evelyne (Journal of Business and Strategic Management, 2025)
Purpose: The study aimed to examine the effect of cost leadership strategies on the financial performance of Savings and Credit Cooperative Organizations (SACCOs) in Kirinyaga County, Kenya. It focused on assessing the impact of operational cost minimization and the influence of technology adoption as cost-saving strategies. Methodology: A descriptive cross-sectional research design was employed, targeting a population of 51 SACCOs in Kirinyaga County. A sample size of 45 SACCOs was determined using Yamane’s (1967) formula. Data were collected from 90 respondents (45 SACCO managers and 45 accountants) through structured surveys and financial record reviews. The study achieved a 100% response rate. Findings: The findings indicated that 96.7% of SACCOs had implemented cost leadership strategies, with 92.2% reporting moderate to significant increases in net income post-adoption. Operational cost minimization significantly contributed to financial gains by enhancing efficiency and reducing overheads. ICT adoption, especially mobile banking (66.7%) and Management Information Systems (25.6%), was identified as a key driver of cost efficiency and improved service delivery. Most SACCOs had utilized ICT for over five years, indicating a mature level of digital integration. The workforce was predominantly aged 31–50 years and held bachelor’s degrees, reflecting a skilled team. However, a shortage of advanced qualifications among professionals was noted as a strategic limitation. Unique Contribution to Theory, Policy and Practice: The study contributes to theory by reinforcing the positive correlation between cost leadership strategies and organizational financial performance. For policy, it emphasizes the need for strategic support and investment in ICT infrastructure for SACCOs. In practice, the study highlights the importance of equipping SACCO personnel with advanced training and expanding digital services to sustain financial growth and competitiveness.